2020
DOI: 10.3171/2019.4.jns19598
|View full text |Cite
|
Sign up to set email alerts
|

Extent of resection of epidermoid tumors and risk of recurrence: case report and meta-analysis

Abstract: OBJECTIVEIntracranial epidermoid tumors are slow-growing, histologically benign tumors of epithelial cellular origin that can be symptomatic because of their size and mass effect. Neurosurgical resection, while the treatment of choice, can be quite challenging due to locations where these lesions commonly occur and their association with critical neurovascular structures. As such, subtotal resection (STR) rather than gross-total resection (GTR) can often be performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 46 publications
1
43
1
Order By: Relevance
“…Although there are no established treatment guidelines, maximal safe surgical resection is generally conducted, and reoperation is often considered for recurrent cases. Due to its benign nature and pathologic simplicity, many studies related to intracranial epidermoid tumors focus on surgical techniques, cranial nerve function preservation, and recurrence after surgery [2,5,8,12,[18][19][20][21]. The EOR was shown to be a signi cant prognostic factor for recurrence in these studies, but there are no known preoperative factors that can predict tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there are no established treatment guidelines, maximal safe surgical resection is generally conducted, and reoperation is often considered for recurrent cases. Due to its benign nature and pathologic simplicity, many studies related to intracranial epidermoid tumors focus on surgical techniques, cranial nerve function preservation, and recurrence after surgery [2,5,8,12,[18][19][20][21]. The EOR was shown to be a signi cant prognostic factor for recurrence in these studies, but there are no known preoperative factors that can predict tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many debates about the optimum extent of resection in intracranial epidermoid tumors [2,5,8,25]. The proliferation of strati ed squamous epithelium is considered to be the cause of tumor recurrence, leading to accumulation of acellular debris such as keratin, protein, and lipid [1,8,9]. Considering the pathogenesis of this tumor, many studies have revealed that complete excision, including of the tumor capsule, reduces the risk of recurrence compared with STR [2,5,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations